Safety, efficacy, and tolerability of efgartigimod in patients with generalised myasthenia gravis (ADAPT): a multicentre, randomised, placebo-controlled, phase 3 trial. Issue 7 (July 2021) - Howard, James F; Bril, Vera; Vu, Tuan; Karam, Chafic; Peric, Stojan; Margania, Temur; Murai, Hiroyuki; Bilinska, Malgorzata; Shakarishvili, Roman; Smilowski, Marek; Guglietta, Antonio; Ulrichts, Peter; et al.
Summary: Background: There is an unmet need for treatment options for generalised myasthenia gravis that are effective, targeted, well tolerated, and can be used in a broad population of patients. We aimed to assess the safety and efficacy of efgartigimod (ARGX-113), a human IgG1 antibody Fc fragment engineered to reduce pathogenic IgG autoantibody levels, in patients with generalised myasthenia gravis. Methods: ADAPT was a randomised, double-blind, placebo-controlled, phase 3 trial done at 56 neuromuscular academic and community centres in 15 countries in North America, Europe, and Japan. Patients aged at least 18 years with generalised myasthenia gravis were eligible to participate in the study, regardless of anti-acetylcholine receptor antibody status, if they had a Myasthenia Gravis Activities of Daily Living (MG-ADL) score of at least 5 (>50% non-ocular), and were on a stable dose of at least one treatment for generalised myasthenia gravis. Patients were randomly assigned by interactive response technology (1:1) to efgartigimod (10 mg/kg) or matching placebo, administered as four infusions per cycle (one infusion per week), repeated as needed depending on clinical response no sooner than 8 weeks after initiation of the previous cycle. Patients, investigators, and clinical site staff were all masked to treatment allocation. The primary endpoint was proportion of acetylcholine receptor antibody-positive patients who were MG-ADL responders (≥2-point MG-ADL improvement sustained for ≥4 weeks) in the first treatment cycle. The primary analysis was done in the modified intention-to-treat population of all acetylcholine receptor antibody-positive patients who had a valid baseline MG-ADL assessment and at least one post-baseline MG-ADL assessment. The safety analysis included all randomly assigned patients who received at least one dose or part dose of efgartigimod or placebo. This trial is registered at ClinicalTrials.gov (NCT03669588); an open-label extension is ongoing (ADAPT+, NCT03770403). Findings: Between Sept 5, 2018, and Nov 26, 2019, 167 patients (84 in the efgartigimod group and 83 in the placebo group) were enrolled, randomly assigned, and treated. 129 (77%) were acetylcholine receptor antibody-positive. Of these patients, more of those in the efgartigimod group were MG-ADL responders (44 [68%] of 65) in cycle 1 than in the placebo group (19 [30%] of 64), with an odds ratio of 4·95 (95% CI 2·21–11·53, p<0·0001). 65 (77%) of 84 patients in the efgartigimod group and 70 (84%) of 83 in the placebo group had treatment-emergent adverse events, with the most frequent being headache (efgartigimod 24 [29%] vs placebo 23 [28%]) and nasopharyngitis (efgartigimod ten [12%] vs placebo 15 [18%]). Four (5%) efgartigimod-treated patients and seven (8%) patients in the placebo group had a serious adverse event. Three patients in each treatment group (4%) discontinued treatment during the study. There were no deaths. Interpretation: Efgartigimod was well tolerated and efficacious in patients with generalised myasthenia gravis. The individualised dosing based on clinical response was a unique feature of ADAPT, and translation to clinical practice with longer term safety and efficacy data will be further informed by the ongoing open-label extension. Funding: argenx.